Comparison of Two Chelator Scaffolds as Basis for Cholecystokinin-2 Receptor Targeting Bimodal Imaging Probes - Gariglio, Giacomo; Bendova, Katerina; Hermann, Martin; Olafsdottir, Asta; Sosabowski, Jane K; Petrik, Milos; von Guggenberg, Elisabeth; Decristoforo, Clemens (Pharmaceuticals (Basel, Switzerland), 2024)
Background/Objectives: Dual-modality probes, combining positron emission tomography (PET) with fluorescence imaging (FI) capabilities in a single molecule, are of high relevance for the accurate staging and guided resection of tumours. We herein present a pair of candidates targeting the cholecystokinin-2 receptor (CCK2R), namely [68Ga]Ga-CyTMG and [68Ga]Ga-CyFMG. In these probes, the SulfoCy5.5 fluorophore and two units of a CCK2R-binding motif are coupled to the chelator acting as a core scaffold, triazacyclononane-phosphinic acid (TRAP), and Fusarinine C (FSC), respectively. Using this approach, we investigated the influence of these chelators on the final properties. Methods: The synthetic strategy to both precursors was based on the stoichiometric conjugation of the components via click chemistry. The characterization in vitro included the evaluation of the CCK2R affinity and internalization in A431-CCK2R cells. Ex vivo biodistribution as well as PET and FI studies were performed in xenografted mice. Results: 68Ga labelling was accomplished with high radiochemical yield and purity for both precursors. A CCK2R affinity in the subnanomolar range of the conjugates and a receptor-specific uptake of the radioligands in cells were observed. In A431-CCK2R/A431-mock xenografted mice, the investigated compounds showed specific accumulation in the tumours and reduced off-target uptake compared to a previously developed compound. Higher accumulation and prolonged retention in the kidneys were observed for [68Ga]Ga-CyTMG when compared to [68Ga]Ga-CyFMG. Conclusions: Despite the promising targeting properties observed, further probe optimization is required to achieve enhanced imaging contrast at early timepoints. Additionally, the results indicate a distinct influence of the chelators in terms of renal accumulation and retention.
Keywords: TRAP; dual-modality imaging agent; gallium-68; SulfoCy5.5; fluorescence guided surgery; cholecystokinin-2 receptor; PET; FSC